Farmer Engagement in Citizen Science for Varietal Diversification Enhanced Adaptive Capacity and Productivity of 25,000 Farmers in India - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
The Seeds for Needs (S4N) initiative has involved over 25,000 farmers as citizen scientists in India, generating positive effects on the level of on-farm varietal diversification, both for rice (+5.,15%) and wheat (+10,.87%). A more diversified production has in turn positively influenced the perceived changes in the yield of the two crops (i.e., +3,.94% rice and 4.,80% wheat). Improved yield trends have enhanced households’ overall capacity to recover from agricultural shocks (+7.,46%).